Pelestarian Tulisan Arab di Era Digital: Sejarah, Tantangan, dan Solusi - Romadona, Rahma Raihana; Angelina, Vitri; Fahrian, M. Zidan (Kalimatuna: Journal of Arabic Research, 2024)
The preservation and conservation of the Arabic language are vital efforts, as demonstrated by various initiatives such as the development of the Arabic script system, the compilation of Islamic sciences' rules, dictionary creation, and the establishment of Arabic language institutions. These endeavors form the foundation for maintaining the relevance and sustainability of the Arabic language in the modern era. This article explores the origins and evolution of the Arabic script, tracing its roots from ancient scripts to the development of various calligraphic styles like Kufic and Naskh. It discusses significant reforms, including the introduction of diacritical marks and vowel signs to enhance readability and comprehension, addressing challenges such as varied pronunciation due to the absence of vowels in the written form. The paper also proposes solutions to these challenges, emphasizing early Arabic education and the integration of modern teaching tools to facilitate language learning and comprehension. Ultimately, the collective responsibility to preserve Arabic language and culture underscores the importance of these efforts in an ever-evolving modern context.